How flat is your detector? Non-uniform annular detector sensitivity in STEM quantification - MacArthur, K; Jones, L; Nellist, P (Institute of Physics Publishing, 2014)
Recording HAADF STEM data on an absolute scale for image quantification is becoming increasingly common. A particular challenge with this method is that most image simulation programs model the detector as being circularly symmetric and exhibiting uniform detection sensitivity across its entire active region. For a real detector this is rarely the case; it then becomes vital to understand how far one's detector deviates from the ideal. Here we investigate a collection of detector maps recorded using hardware from each of the current major manufacturers. Using these maps we compare their different asymmetries and any non-uniformities in their sensitivity. To facilitate this we define the parameters; 'flatness', 'roundness', 'smoothness' and 'ellipticity', evaluate each hardware with respect to these and rank them. © Published under licence by IOP Publishing Ltd.